2011
DOI: 10.2527/jas.2010-3375
|View full text |Cite
|
Sign up to set email alerts
|

TRIENNIAL GROWTH SYMPOSIUM: A review of science leading to host-targeted antibody strategies for preventing growth depression due to microbial colonization1,2

Abstract: In this review, the science used to develop host-targeted therapies for improving animal growth and feed efficiency is presented. In contrast to targeting the microbiota of the host, endogenous host proteins are targeted to regulate an overactive inflammatory response in the host. Activation of the immune/inflammatory systems of an animal is costly in terms of growth and feed efficiency. For example, reduced rates of BW gain and poorer feed efficiency in vaccinated animals compared with nonvaccinated animals h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…There is moderate expression of the receptor for ghrelin, growth hormone secretagoguereceptor (GHS-R), in the crop of Japanese quail (Kitazwa et al, 2009). Moreover, crop emptying is also influenced by the brain; it is depressed by intracerebral injections of gastrin , glucagon-like peptide-1, neuromedins B, C or bombesin (Tachibana et al, 2003;2010). It is not clear whether these effects are mediated through the gastrin releasing peptide or the bombesin receptors.…”
Section: Control Of Crop Functioningmentioning
confidence: 96%
See 1 more Smart Citation
“…There is moderate expression of the receptor for ghrelin, growth hormone secretagoguereceptor (GHS-R), in the crop of Japanese quail (Kitazwa et al, 2009). Moreover, crop emptying is also influenced by the brain; it is depressed by intracerebral injections of gastrin , glucagon-like peptide-1, neuromedins B, C or bombesin (Tachibana et al, 2003;2010). It is not clear whether these effects are mediated through the gastrin releasing peptide or the bombesin receptors.…”
Section: Control Of Crop Functioningmentioning
confidence: 96%
“…The growth rate of GF poultry is 10-20% greater than that of conventional poultry. This is probably due to the lack of adverse effects of microbial colonisation of the gastro-intestinal tract and/or activation of gastro-intestinal immune/inflammatory responses (reviewed Cook, 2010).…”
Section: Environmental Factors and Gastro-intestinal Tract Developmentmentioning
confidence: 99%
“…To this end, the use of IgY targeting specific molecules involved in inflammation and animal growth has been described. Antibodies directed against the gut neuropeptides cholecystokinin and neuropeptide Y, believed to be involved in regulating appetite, as well as the enzyme PLA 2 , which plays a role in the production of the inflammatory mediators prostaglandins and leukotrienes, have both been shown to improve growth and feed efficiency when fed to chickens (reviewed in Cook 2004Cook , 2010. Similarly, Mahdavi et al (2010) found that feeding yolk powder containing IgY against E. coli O78:K80 to chickens improved intestinal health and feed conversion ratio, and enhanced intestinal responses upon oral challenge.…”
Section: Igy Use In Veterinary Applicationsmentioning
confidence: 99%
“…Upon activation of the immune system and the APR, an organism diverts nutrients away from growth and development, redirecting it into defense processes (Johnson, 1997) followed by immediate decrease in feed intake, wasting of skeletal muscle, increased lipolysis and production of acute-phase proteins (APP) by the liver, plasma mineral alterations, fever, and changes in behavior (Johnson, 1997;Cook, 2011;Cooke and Bohnert, 2011). One theory hypothesizes that pathogens and lipopolysaccharides (LPS) translocate into the bloodstream through activation of secretory phospholipase A 2 (sPLA 2 ) in the intestinal lumen, and once in the bloodstream, LPS stimulates leukocyte production of proinflammatory cytokines with further activation of the APR, leading to physiological responses that have direct effects on animal performance (Cook, 2011). Feed efficiency (FE) and growth was improved in a series of studies with poultry, swine, and fish using an egg-derived antibody against sPLA 2 (anti-phospholipase A 2 antibody [aPLA 2 ]) as a feed additive (Yang et al, 2003;Cook, 2004Cook, , 2011Barry and Yang, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One theory hypothesizes that pathogens and lipopolysaccharides (LPS) translocate into the bloodstream through activation of secretory phospholipase A 2 (sPLA 2 ) in the intestinal lumen, and once in the bloodstream, LPS stimulates leukocyte production of proinflammatory cytokines with further activation of the APR, leading to physiological responses that have direct effects on animal performance (Cook, 2011). Feed efficiency (FE) and growth was improved in a series of studies with poultry, swine, and fish using an egg-derived antibody against sPLA 2 (anti-phospholipase A 2 antibody [aPLA 2 ]) as a feed additive (Yang et al, 2003;Cook, 2004Cook, , 2011Barry and Yang, 2008). However, the use of aPLA 2 as a feed additive for cattle diets has not been reported.…”
Section: Introductionmentioning
confidence: 99%